2008
DOI: 10.1128/aac.01227-07
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hepatitis C Virus (HCV) RNA Polymerase by DNA Aptamers: Mechanism of Inhibition of In Vitro RNA Synthesis and Effect on HCV-Infected Cells

Abstract: We describe here the further characterization of two DNA aptamers that specifically bind to hepatitis C virus (HCV) RNA polymerase (NS5B) and inhibit its polymerase activity in vitro. Although they were obtained from the same selection procedure and contain an 11-nucleotide consensus sequence, our results indicate that aptamers 27v and 127v use different mechanisms to inhibit HCV polymerase. While aptamer 27v was able to compete with the RNA template for binding to the enzyme and blocked both the initiation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…It seems possible that the inhibitory effect of AO-01 was relatively strong during the early phase after the transfection, while later during the 3-day period, virus production may be more and more undisturbed. A DNA aptamer against the NSB5 protein of hepatitis C virus has a dissociation constant of 132 nM, which is similar to the K d of aptamer AO-01, and reduced viral mRNA levels by 90% in a cell culture system (32). Another possible explanation besides the short half-life for the relatively weak inhibition of budding by aptamer AO-01 is that the MBD of mature HBV capsids competent for budding may have a structure different from that of the MBD of recombinant capsids lacking the C-terminal domain.…”
Section: Discussionmentioning
confidence: 99%
“…It seems possible that the inhibitory effect of AO-01 was relatively strong during the early phase after the transfection, while later during the 3-day period, virus production may be more and more undisturbed. A DNA aptamer against the NSB5 protein of hepatitis C virus has a dissociation constant of 132 nM, which is similar to the K d of aptamer AO-01, and reduced viral mRNA levels by 90% in a cell culture system (32). Another possible explanation besides the short half-life for the relatively weak inhibition of budding by aptamer AO-01 is that the MBD of mature HBV capsids competent for budding may have a structure different from that of the MBD of recombinant capsids lacking the C-terminal domain.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their inhibitory effects against HCV should be carefully tested using the genotype 3a cell culture system that has been recently developed [76] . Bellecave et al [77] also reported DNA aptamers against HCV NS5B, and their aptamers inhibited HCV JFH-1 replication and viral particle formation in the cell culture system. However, those aptamers were not examined with regard to cell toxicity profiles, distribution in animals, or side effects during long-term treatment.…”
Section: Ns5b Targeting Aptamersmentioning
confidence: 94%
“…Hairpin ribozyme Cleave target RNAs 5'-UTR [24,28] , 3'-UTR [28] , and core region [24] Tested in in vitro [24] and in cell culture model [28] HDV ribozyme 5'-UTR [30] Tested in in vitro Hammerhead ribozyme (Hepatozyme) 5'-UTR [33][34][35] Completion of phase Ⅱ DNAzyme 5'-UTR [41] , core and NS5B region [39,40] Tested in in vitro and in cell culture model RNase P 5'-UTR [45][46][47] Splicing riboyme Selectively replace target RNAs with desirable RNAs 5'-UTR [51] Allosteric ribozyme Inhibit HCV replication [54] or cleave HCV RNA [31] through recognizing ligands miR-122 [54] and 5'-UTR [31] Aptamer Bind to target molecule and function as decoys and/or inhibitors NS3 [68][69][70] NS5B [75][76][77][78] E1E2 [79] Viral RNA [80,81] …”
Section: Mode Of Action Target Statusmentioning
confidence: 99%
“…Bellecave et al reported DNA aptamers that inhibit HCV JFH-1 replication and viral particle formation in a cell culture system (53). However, those DNA aptamers were not examined with regard to cell toxicity profiles, distribution in animals, or side effects during long-term treatment.…”
Section: Discussionmentioning
confidence: 99%